Energy and emissions saving potential of additive manufacturing: the case of lightweight aircraft components. (1st November 2016) - Huang, Runze; Riddle, Matthew; Graziano, Diane; Warren, Joshua; Das, Sujit; Nimbalkar, Sachin; Cresko, Joe; Masanet, Eric
Abstract: Additive manufacturing (AM) holds great potential for improving materials efficiency, reducing life-cycle impacts, and enabling greater engineering functionality compared to conventional manufacturing (CM), and AM has been increasingly adopted by aircraft component manufacturers for lightweight, cost-effective designs. This study estimates the net changes in life-cycle primary energy and greenhouse gas emissions associated with AM technologies for lightweight metallic aircraft components through the year 2050, to shed light on the environmental benefits of a shift from CM to AM processes in the U.S. aircraft industry. A systems modeling framework is presented, with integrates engineering criteria, life-cycle environmental data, aircraft fleet stock and fuel use models under different AM adoption scenarios. Estimated fleet-wide life-cycle primary energy savings at most reach 70-173 million GJ/year in 2050, with cumulative savings of 1.2–2.8 billion GJ. Associated cumulative GHG emission reductions were estimated at 92.1–215.0 million metric tons. In addition, thousands of tons of aluminum, titanium and nickel alloys could be potentially saved per year in 2050. The results indicate a significant role of AM technologies in helping society meet its long-term energy use and GHG emissions reduction goals, and highlight barriers and opportunities for AM adoption for the aircraft industry. Highlights: We estimate the energy and GHG saving potentials of AM lightweight aircraft parts. Model includes adoption estimation, LCI, fleet stock and scenarios through 2050. Total fleet-wide life-cycle primary energy savings potentials is 1.2–2.8 billing GJ. Associated cumulative emission reduction potentials of CO2 e is 93–217 million tons. Thousands tones of Al, Ti and Ni alloys could be saved per year in 2050.